Abuse and humiliation in the delivery room: Prevalence and associated factors of obstetric violence in Ghana - Yalley, Abena Asefuaba; Abioye, Dare; Appiah, Seth Christopher Yaw; Hoeffler, Anke (Frontiers in Public Health, 2023)
Background: Abuse and mistreatment of women during childbirth is a major barrier to facility-based delivery, putting women at risk of avoidable complications, trauma and negative health outcomes including death. We study the prevalence of obstetric violence and its associated factors in the Ashante and Western Regions of Ghana. Methodology: A facility-based cross-sectional survey was conducted in eight public health facilities from September to December 2021. Specifically, close-ended questionnaires were administered to 1,854 women, aged 15 to 45 who were delivered in the health facilities. The data collected include the sociodemographic attributes of women, their obstetric history and experiences of obstetric violence based on the seven typologies according to the categorization by Browser and Hills. Findings: We find that about two in every three women (65.3%) experience obstetric violence. The most common form of obstetric violence is non-confidential care (35.8%), followed by abandoned care (33.4%), non-dignified care (28.5%) and physical abuse (27.4%). Furthermore, 7.7% of women were detained in health facilities for their inability to pay their bills, 7.5% received non-consented care while 11.0% reported discriminated care. A test for associated factors of obstetric violence yielded few results. Single women (OR 1.596, 95% CI 1.172-2.172) and women who reported birth complications (OR 3.187, 95% CI 2.361-4.301) were more likely to experience obstetric violence compared with married women and women who had no birth complications. In addition, teenage mothers (OR 2.575, 95% CI 1.484-4.468) were more likely to experience physical abuse compared to older mothers. Rural versus urban location, employment status, gender of birth attendant, type of delivery time of delivery, the ethnicity of the mothers and their social class were all not statistically significant Conclusion: The prevalence of obstetric violence in the Ashante and Western Regions was high and only a few variables were strongly associated with obstetric violence, suggesting that all women are at risk of abuse.